The Effect of Work Schedule Control on Volunteering among Early Career Employees - Noemi Mantovan; Robert M. Sauer; John Wilson (Institute of Labor Economics (IZA), 2021)
Recent trends in the labor market see increasing numbers of workers having to deal with "schedule precarity" including volatile hours, rotating shift work, unpredictable work hours and lack of choice on the part of the employee. These trends are of concern to those interested in fostering levels of civic engagement because they potentially limit volunteering. This study uses data from the National Longitudinal Survey of Youth 1997 (NLSY97) containing information on work schedules in 2011 and 2013 among employees to determine the effect of changes in work schedules on becoming a volunteer using transition regressions. We investigate interactions between work schedule measures and pay structure because workers paid by the hour have lower volunteer rates than salaried workers. The study finds that, while three of the schedule dimensions are unrelated to volunteering, transitioning towards more schedule control has a positive effect on volunteering. However, interaction analysis shows this positive effect is confined to salaried workers whereas for hourly paid workers the effect is negative. The results support the idea that having more freedom to set one's work schedule reduces work-life conflict but suggest that this positive effect is limited to those who can take advantage of it.
Keywords: J10; J20; J30; 330; volunteer work; precarious employment; work-schedules; pay structure